Adhesive layer, adhesive sheet using same, laminate, and flexible image display device

By using a specific adhesive layer composition in a folding display, the problem of whitening and offsetting of the adhesive layer in the bent area is solved, and a flexible image display device with high precision, good visual recognition and bending is realized.

CN119907843APending Publication Date: 2025-04-29아티엔스가부시키가이샤 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280100277.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In a foldable display, when colorless polyimide is used as the adherent object, the adhesive layer may easily whiten or foam at the bent part, and the adhesive layer may shift after repeated bending, resulting in poor bending.

Method used

An adhesive layer having a gel fraction of 55% to 90%, a storage elastic modulus of 0.1 MPa or more and 8 MPa or less was used to form an adhesive layer having a high recovery rate and good bending performance through an adhesive composition containing an acrylic adhesive and a hardener.

Benefits of technology

A flexible image display device with high precision is achieved which is not easy to whiten the curved parts and does not easily shift the ends, ensuring good visual recognition and contrast, and also has good bending properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005320858190000131
    Figure BDA0005320858190000131
  • Figure BDA0005320858190000171
    Figure BDA0005320858190000171
  • Figure BDA0005320858190000181
    Figure BDA0005320858190000181
Patent Text Reader

Abstract

An adhesive layer used in a flexible image display device has a gel fraction of 55-90%, a storage elastic modulus at-30 DEG C of 0.1-8 MPa, a deformation amount alpha of 100-800% when a strain of 20 kPa is imparted for 5 minutes by a parallel plate at 25 DEG C using a measurement probe of phi 8 mm by a rheometer, and the adhesive layer is represented by the following formula: recovery rate = (alpha-beta) / alpha * 100 (beta represents a value after measurement of alpha, and alpha represents a value after measurement of alpha). The adhesive layer is formed using an adhesive composition containing an acrylic adhesive and a curing agent, and has a recovery rate of 70% or more, said recovery rate being calculated using an amount of residual deformation after 5 minutes after a strain of 0 kPa) (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an adhesive layer for a flexible image display device, an adhesive sheet using the same, a laminate, and a flexible image display device. Background Art

[0002] In recent years, input devices that combine image display devices such as liquid crystal display (LCD) or organic electroluminescence (organic EL (electroluminescence)) display (organic light-emitting diode (organic light-emitting diode, OLED)) with touch panels have become popular. The transparent conductive film used in the touch panel is laminated on a supporting glass or other components via an adhesive layer. In addition, the polarizing plate film used in the image display device is attached to the liquid crystal module or organic EL module via an adhesive layer.

[0003] As the image display device, flat panel displays using glass substrates are the mainstream, but in recent years, flexible displays such as foldable displays and rollable displays using flexible substrates such as plastics have been developed. Compared with conventional flat panel displays using glass substrates, such flexible displays have various advantages such as lightness, thinness, flexibility, and excellent design.

[0004] The adhesive layer has always been required to have the property of not bubbling or peeling in a high temperature environment or a high temperature and high humidity environment, but in recent years, it has been required to have flexibility. The so-called flexibility, for example, in a foldable display, is the adaptability (bendability) corresponding to the bending of the display so that it can be used in a foldable display. Generally speaking, as bendability, it is required to have the property of not bubbling, floating or peeling when repeatedly bent (dynamic bendability).

[0005] To solve the above problems, Patent Document 1 discloses an adhesive whose object is to suppress the occurrence of floating or peeling of the adhesive layer even when bent repeatedly. Patent Document 2 discloses an adhesive for a bending element having a storage elastic modulus G' at -20°C and 85°C within a specific numerical range.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-513451

[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-139034 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, in foldable displays, colorless polyimide is used as an adherend in terms of strength and transparency. If a laminate formed by laminating a colorless polyimide and an adhesive layer is bent, the adhesive may float, especially at the bent portion, or foaming may occur in the adhesive layer and whiten. In addition, if it is bent repeatedly, the adhesive layer may deviate at the end, and the adhesive layer may also contact the surrounding components, resulting in poor bendability.

[0012] The present disclosure is made in view of the above problems, and its object is to provide an adhesive layer used in a flexible image display device, in which the bent portion is not easily whitened and the adhesive is not easily offset even if it is repeatedly bent, an adhesive sheet using the same, a laminate, and a flexible image display device.

[0013] Technical means of solving problems

[0014] The present inventors have conducted extensive studies to achieve the above-mentioned purpose and have found that the following embodiments can solve the problems of the present invention, thereby completing the present invention.

[0015] ·The adhesive layer disclosed in the present invention is used for a flexible image display device, in which the gel fraction of the adhesive layer is 55% to 90%, the storage elastic modulus at -30°C is greater than 0.1MPa and less than 8MPa, the deformation α when a strain of 20kPa is applied for 5 minutes using a parallel plate at 25°C using a rheometer using a measuring probe of φ8mm is 100% to 800%, and the recovery rate obtained by the formula: Recovery rate = (α-β) / α×100 (β represents the residual deformation after 5 minutes after the strain is set to 0kPa after measuring α)···(1) is greater than 70%, and the adhesive layer is formed using an adhesive composition comprising an acrylic adhesive and a hardener.

[0016] The adhesive sheet of the present disclosure includes the adhesive layer and a separator.

[0017] The laminated body of the present disclosure is obtained by attaching the adhesive layer to an adherend.

[0018] The flexible image display device of the present disclosure includes the laminated body.

[0019] Effects of the Invention

[0020] The present disclosure provides an adhesive layer, an adhesive sheet and a laminated body used for a flexible image display device that is not prone to whitening at a bent portion and is not prone to displacement at an end portion and is highly accurate. Thus, a flexible image display device that has good visibility and contrast even when bent and good bendability can be provided. DETAILED DESCRIPTION

[0021] The following description of the preferred embodiments is merely illustrative in nature and is not intended to limit the present invention, its applications, or its uses.

[0022] The numerical values ​​determined in this specification are values ​​obtained by the methods disclosed in the embodiments or examples. Adhesive sheets have the same meaning as adhesive films, adhesive tapes, adhesive labels, etc. Unless otherwise specified, the various formulation components in the adhesive can be used independently or in combination of two or more. (Meth)acrylic acid refers to acrylic acid or methacrylic acid, and (meth)acrylate refers to acrylate or methacrylate.

[0023] <Adhesive layer>

[0024] The adhesive layer of this embodiment is used for a flexible image display device. Specifically, the adhesive layer is preferably used for a laminated body constituting a flexible image display device, and an adhesive sheet used when forming the laminated body. The adhesive layer is preferably a single layer, and is also preferably in a form in which a core material is provided therebetween. Examples of the core material include polyethylene terephthalate (PET), polyimide, and the like.

[0025] [Adhesive]

[0026] The adhesive layer is formed using an acrylic adhesive containing a (meth)acrylic acid copolymer as a main component. The (meth)acrylic acid copolymer constituting the acrylic adhesive preferably has units derived from a monomer containing a reactive functional group containing a functional group that can be cross-linked with a hardener. By promoting cross-linking between the (meth)acrylic acid copolymer and the hardener in the adhesive layer formed by the adhesive, the adhesive layer is hardened to form a cross-linked structure. In addition, the adhesive may be composed only of an acrylic adhesive (which may contain one or more (meth)acrylic acid copolymers), or it may be used in combination with other adhesives. As other adhesives, for example, urethane adhesives containing urethane resins as main components, rubber adhesives containing rubber resins as main components, etc. can be listed.

[0027] The weight average molecular weight (Mw) of the adhesive (copolymer or resin constituting the adhesive) is preferably 800,000 to 2,000,000, more preferably 800,000 to 1,800,000, and still more preferably 1,000,000 to 1,500,000. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) in terms of polystyrene.

[0028] [Acrylic adhesive]

[0029] The (meth)acrylic copolymer constituting the acrylic adhesive is preferably a copolymer of a monomer mixture containing an alicyclic monomer and / or an acrylic monomer having a straight-chain alkyl group with a carbon number of 10 to 20 (hereinafter also referred to as a "C10-20 straight-chain alkyl monomer"), and an acrylic monomer having a branched-chain alkyl group with a carbon number of 6 or more (hereinafter also referred to as a "C6≦branched alkyl monomer"). In other words, the monomer mixture used as a raw material for the (meth)acrylic copolymer is preferably: a monomer mixture containing an alicyclic monomer and a "C6≦branched alkyl monomer"; a monomer mixture containing a "C10-20 straight-chain alkyl monomer" and a "C6≦branched alkyl monomer"; and a monomer mixture containing an alicyclic monomer, a "C10-20 straight-chain alkyl monomer" and a "C6≦branched alkyl monomer". These monomers may be used alone or in combination of two or more.

[0030] 《Alicyclic Monomers》

[0031] Alicyclic monomers refer to monomers having polymerizable functional groups containing unsaturated double bonds such as (meth) acryloyl or vinyl, and having a base containing an alicyclic structure. Here, "base containing an alicyclic structure" refers to a portion containing at least one alicyclic structure, sometimes referred to as "alicyclic group" below. As an alicyclic group, hydrocarbon groups or hydrocarbonoxy groups with an alicyclic structure can be cited. The monomer mixture used in the raw materials of the (meth) acrylic copolymer contains an alicyclic monomer, and the adhesion and recovery rate of the adhesive sheet are improved. It is believed that the alicyclic monomer contributes to the improvement of cohesive force as a hard segment, so the peel strength and recovery rate of the adhesion of the adhesive sheet are improved. Alicyclic monomers can be cited, for example: isobornyl (meth) acrylate, cyclohexyl (meth) acrylate, dicyclopentadienyl (meth) acrylate, cyclododecyl (meth) acrylate, methylcyclohexyl (meth) acrylate, trimethylcyclohexyl (meth) acrylate, etc. Among these, isobornyl (meth) acrylate is preferred, and isobornyl acrylate is more preferred.

[0032] The content of the alicyclic monomer is preferably 1% by mass or more and 20% by mass or less relative to the total amount of the monomer mixture, more preferably 5% by mass or more and 15% by mass or less. If the content of the alicyclic monomer is 1% by mass or more, the hardness and softness of the adhesive sheet can be taken into account at a higher level. In addition, if the content of the alicyclic monomer is 20% by mass or less, the bendability of the adhesive sheet is further improved.

[0033] 《Acrylic acid monomer having a linear alkyl group having 10 to 20 carbon atoms》

[0034] An acrylic monomer having a straight-chain alkyl group having 10 to 20 carbon atoms (C10 to 20 straight-chain alkyl monomer) refers to a monomer having a straight-chain alkyl group having 10 to 20 carbon atoms in the molecule. The number of carbon atoms in the straight-chain alkyl group is preferably 12 to 20. Examples of "C10 to 20 straight-chain alkyl monomers" include: decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. Among these, dodecyl (meth)acrylate and octadecyl (meth)acrylate are preferred, and dodecyl acrylate and octadecyl acrylate are more preferred.

[0035] The content of "C10-20 straight-chain alkyl monomer" is preferably 5% by mass or more and 50% by mass or less, and more preferably 7% by mass or more and 40% by mass or less, relative to the total amount of the monomer mixture (100% by mass), If the content of "C10-20 straight-chain alkyl monomer" is 5% by mass or more, the hardness and softness of the adhesive sheet can be taken into account at a higher level. In addition, if the content of "C10-20 straight-chain alkyl monomer" is 50% by mass or less, the bendability of the adhesive sheet is further improved.

[0036] 《Acrylic acid monomer having a branched chain alkyl group with 6 or more carbon atoms》

[0037] An acrylic monomer having a branched alkyl group with 6 or more carbon atoms (C6≦branched alkyl monomer) refers to a monomer having a branched alkyl group with 6 or more carbon atoms in the molecule. The number of carbon atoms in the branched alkyl group is preferably 6 to 10. Examples of "C6≦branched alkyl monomer" include: isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, etc. Among these, 2-ethylhexyl (meth)acrylate is preferred, and 2-ethylhexyl acrylate is more preferred.

[0038] Relative to the total amount of 100 mass % of the monomer mixture, the content of "C6≦branched alkyl monomer" is preferably 30 mass % or more, more preferably 35 mass % or more, and the upper limit is preferably 95 mass % or less, more preferably 90 mass % or less. If the content of "C6≦branched alkyl monomer" is 30 mass % or more, the hardness and softness of the adhesive sheet can be taken into account at a higher level. In addition, if the content of "C6≦branched alkyl monomer" is 95 mass % or less, the bendability of the adhesive sheet is further improved. In addition, relative to the total amount of 100 mass % of the monomer mixture containing alicyclic monomers and "C6≦branched alkyl monomer", the content of "C6≦branched alkyl monomer" is preferably 50 mass % or more and 95 mass % or less, more preferably 55 mass % or more and 90 mass % or less. The content of the "C6≦branched alkyl monomer" is preferably 30% by mass or more and 95% by mass or less, and more preferably 35% by mass or more and 90% by mass or less, relative to 100% by mass of the total amount of the monomer mixture containing the "C10-20 linear alkyl monomer" and the "C6≦branched alkyl monomer".

[0039] The monomer mixture used as the raw material of the (meth)acrylic acid copolymer may contain, in addition to the above-mentioned monomers, a macromonomer, a monomer having a hydroxyl group, a monomer having a carboxyl group, a monomer having an amino group, an acrylic monomer having a linear alkyl group having 1 to 9 carbon atoms or a branched alkyl group having 3 to 9 carbon atoms, etc. These monomers may be used alone or in combination of two or more.

[0040] Macromonomer

[0041] The macromonomer is a macromonomer having a number average molecular weight (Mn) of 3000 to 25000. The number average molecular weight of the macromonomer is preferably 4000 to 10000, more preferably 5000 to 8000. By setting the molecular weight within the above range, whitening of the curved portion is improved.

[0042] Examples of commercially available macromonomers having the above number average molecular weight include a macromonomer having a methacryloyl group at a molecular terminal and a polymer chain of polymethyl methacrylate (product name: AA-6, AA-6S, number average molecular weight 6,000; manufactured by Toagosei Co., Ltd.), a macromonomer having a polymer chain of polystyrene (product name: AS-6S, AS-6, number average molecular weight 6,000; manufactured by Toagosei Co., Ltd.), a macromonomer having a polymer chain of a styrene / acrylonitrile copolymer (product name: AN-6S, number average molecular weight 6,000; manufactured by Toagosei Co., Ltd.), a macromonomer having a polymer chain of polybutyl acrylate (product name: AB-6, number average molecular weight 6,000; manufactured by Toagosei Co., Ltd.), and a macromonomer having a polymer chain of polybutyl acrylate (product name: AB-8, number average molecular weight 8,000; manufactured by Toagosei Co., Ltd.).

[0043] The content of the macromonomer is preferably 1% by mass or more and 10% by mass or less, and more preferably 4% by mass or more and 8% by mass or less, relative to the total amount of the monomer mixture (100% by mass). If the content of the macromonomer is 1% by mass or more, hardness and softness can be achieved at a higher level. In addition, if the content of the macromonomer is 10% by mass or less, the bendability is further improved.

[0044] 《Monomers having hydroxyl groups》

[0045] The monomer having a hydroxyl group is not limited as long as it has a hydroxyl group in the molecule, and examples thereof include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc. Among these, 4-hydroxybutyl (meth)acrylate is preferred, and 4-hydroxybutyl acrylate is more preferred.

[0046] 《Monomers with carboxyl groups》

[0047] The monomer having a carboxyl group is not limited as long as it is a monomer having a carboxyl group in the molecule, and specifically includes: (meth)acrylic acid, p-carboxybenzyl acrylate, β-carboxyethyl acrylate, maleic acid, monoethyl maleate, itaconic acid, citraconic acid, fumaric acid, etc. Among these, (meth)acrylic acid is preferred, and acrylic acid is more preferred.

[0048] 《Monomers with amino groups》

[0049] Examples of the monomer having an amino group include monoalkylamino (meth)acrylates such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate; and (meth)acrylamide. Among these, (meth)acrylamide is preferred, and acrylamide is more preferred.

[0050] 《Acrylic acid monomer having a linear alkyl group having 1 to 9 carbon atoms or a branched alkyl group having 3 to 9 carbon atoms》

[0051] Examples of the acrylic monomer having a linear alkyl group having 1 to 9 carbon atoms or a branched alkyl group having 3 to 9 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and nonyl (meth)acrylate.

[0052] [Synthesis of (meth)acrylic acid copolymer (polymerization of monomer mixture)]

[0053] The polymerization of the monomer mixture containing the monomer can be applied to known polymerization methods such as solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization. The polymerization initiator used in the polymerization is preferably a free radical polymerization initiator. As a free radical polymerization initiator, commonly known peroxides, azo compounds (2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile, AIBN), etc. can be used. Relative to 100 parts by mass of the monomer mixture, the polymerization initiator is preferably used in an amount of 0.01 to 10 parts by mass, and more preferably 0.1 to 2 parts by mass. As described above, a (meth)acrylic acid copolymer (acrylic adhesive containing it) as a copolymer of the monomer mixture is obtained.

[0054] [Hardener]

[0055] The acrylic adhesive is preferably used together with a hardener. In other words, the adhesive layer preferably contains an acrylic adhesive and a hardener. Examples of the hardener include epoxy hardeners, isocyanate hardeners, aziridine hardeners, amine hardeners, thiol hardeners, and anhydride hardeners. The hardeners may be used alone or in combination of two or more. Among the hardeners, epoxy hardeners and isocyanate hardeners are preferred.

[0056] 《Aromatic compounds》

[0057] The curing agent is preferably an aromatic compound. For example, as an epoxy aromatic compound, there can be listed: phenol novolac type, cresol novolac type, bisphenol A type, bisphenol F type, bisphenol S type, trisphenol methane type, tetraphenol ethane type, bixylenol type, biphenol type and other heterocyclic epoxies. As an isocyanate aromatic compound, there can be listed: toluene diisocyanate, methylene diphenyl diisocyanate, xylene diisocyanate, tetramethyl xylene diisocyanate and their allophanate, biuret, isocyanurate, prepolymer and adduct. As an amine aromatic compound, there can be listed: amines containing heteroaromatic rings such as m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, benzyldimethylamine, dimethylaminomethylbenzene, phenol resin, phenol novolac resin, etc. Examples of the thiol-based aromatic compound include tertiary amines such as N,N-dimethylaniline, mercaptobenzimidazole, etc. Examples of the acid anhydride-based aromatic compound include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, etc.

[0058] The content of the hardener (hereinafter also referred to as "hardener amount") relative to the total amount of the adhesive 100 mass % is preferably 0.1 mass % to 80 mass %, more preferably 0.1 mass % to 30 mass %, and further preferably 0.1 mass % to 10 mass %. By making the hardener amount within the above range, the cohesion can be improved and the recovery rate can be increased.

[0059] <Adhesive layer characteristics>

[0060] Here, the adhesive layer of this embodiment contains an acrylic adhesive composed of a (meth) acrylic acid copolymer as a copolymer of the monomer mixture, and a hardener, and therefore satisfies the prescribed gel fraction, elastic modulus, deformation amount α, and recovery rate. When the adhesive layer that satisfies all four characteristics is bent and used in a flexible image display device bonded to an adherend, whitening of the bent portion and deviation of the end portion can be suppressed. In addition, the adhesive layer has high adhesion to the adherend.

[0061] [Gel fraction]

[0062] The gel fraction of the adhesive layer is 55% to 90%, preferably 55% to 90%. By making the gel fraction within the range, the whitening of the curved part is improved. The gel fraction can be controlled within the range by, for example, adjusting the curing time and temperature when forming the adhesive layer; adjusting the amount of hardener used as the raw material of the adhesive forming the adhesive layer, the macromonomer (especially the macromonomer with a number average molecular weight of about 6000), the acrylic monomer with an alkyl group with more than 10 carbon atoms, the monomer with a hydroxyl group, etc.

[0063] [Storage elastic modulus at -30°C]

[0064] The storage elastic modulus of the adhesive layer at -30°C (hereinafter also referred to as "storage elastic modulus") is 8 MPa or less, preferably 5 MPa or less. By making the storage elastic modulus within the range, the whitening of the bent portion can be suppressed. In addition, the lower limit of the storage elastic modulus is 0.1 MPa or more, preferably 0.15 MPa or more. The storage elastic modulus can be adjusted, for example, by using a "C6≦branched alkyl monomer" in the raw material (monomer mixture) of the adhesive forming the adhesive layer.

[0065] [Deformation α]

[0066] The deformation amount α of the adhesive layer is more than 100% and less than 800%, preferably more than 200% and less than 750%, more preferably more than 250% and less than 700%, and further preferably more than 300% and less than 600%. By making the deformation amount α of the adhesive layer within the range, the displacement of the end is suppressed. Here, the deformation amount α of the adhesive layer in the present disclosure refers to the deformation amount when a 20kPa strain is applied to an adhesive layer with a thickness of 1mm at 25°C using a parallel plate by a rheometer using a φ8mm measuring probe for 5 minutes. The deformation amount α, for example, increases when the amount of hardener used to form the adhesive raw material is reduced, and the deformation amount α decreases when the amount of hardener is increased.

[0067] [Recovery rate]

[0068] The recovery rate of the adhesive layer is 70% or more, preferably 75% or more, and more preferably 80% or more. When the recovery rate is 70% or more, whitening of the bent portion is improved. The recovery rate in the present disclosure is a value calculated by formula (1).

[0069] [Formula 1]

[0070] Recovery rate = (α-β) / α×100···(1)

[0071] In formula (1), β represents the residual deformation α after 5 minutes after the strain is set to 0 kPa after measuring α using the rheometer. The recovery rate is improved by increasing the amount of hardener used as the adhesive raw material for forming the adhesive layer, or increasing the content ratio of "C6≦branched alkyl monomer" and macromolecular monomer (especially macromolecular monomer with a number average molecular weight of about 6000).

[0072] [Adhesion to adherend]

[0073] The adhesive force of the adhesive layer to the adherend (particularly colorless polyimide) is preferably 10N / 25mm or more and 50N / 25mm or less, more preferably 15N / 25mm or more and 45N / 25mm or less. By being set to the range, the offset of the end at the interface of the adherend and the adhesive layer is suppressed. In order to make the adhesive force within the range, corona treatment or plasma treatment can be implemented on the adherend surface.

[0074] "Sticked Object"

[0075] Examples of adherends include colorless polyimide, ultra-thin glass, polyethylene terephthalate (PET) film, etc. Colorless polyimide refers to a polyimide film having a transmittance of 80% or more at 400 nm to 700 nm and a glass transition temperature of 250° C. or more. The thickness of the colorless polyimide is preferably 10 μm or more and 200 μm or less, and more preferably 20 μm or more and 100 μm or less.

[0076] <Formation of Adhesive Layer>

[0077] The adhesive layer is formed by an adhesive composition. The adhesive composition comprises an adhesive and a hardener, and is mixed with an adhesion imparting resin, a solvent, etc. as required. As a method for forming an adhesive layer, for example, a method of applying the adhesive composition to a spacer, drying and removing the solvent, etc., to form an adhesive layer, etc., can be cited. On the other hand, the adhesive composition can also be directly applied to the adherend, and then dried to remove the solvent, etc., to form an adhesive layer.

[0078] The drying temperature of the solvent is preferably 40° C. to 200° C., more preferably 50° C. to 180° C., and still more preferably 70° C. to 170° C. By setting the drying temperature of the solvent to be within the above range, an adhesive layer having excellent adhesive properties can be obtained.

[0079] The drying time of the solvent can be appropriately adopted, and the drying time of the solvent is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 10 minutes, and further preferably 10 seconds to 5 minutes.

[0080] Various methods can be used as a coating method for the adhesive composition, for example, roll coating, lick roller coating, gravure coating, reverse coating, roller brushing, spray coating, dip roller coating, rod coating, blade coating, air knife coating, curtain coating, die lip coating, extrusion coating using a die coater, etc.

[0081] The thickness of the adhesive layer is preferably 5 μm or more and 150 μm or less, more preferably 15 μm or more and 100 μm or less. The adhesive layer may be a single layer or may be a laminate of adhesives with different compositions. As long as the thickness of the adhesive layer (the total thickness in the case of a laminated structure) is within the range, bending will not be hindered, and it is also a preferred form in terms of adhesion. On the other hand, when the thickness exceeds 150 μm, the polymer chains in the adhesive layer are easy to move during repeated bending, and deterioration becomes serious, so peeling may occur. When the thickness is less than 5 μm, the stress during bending cannot be relieved, and breakage may occur.

[0082] <Adhesive sheet for flexible image display device>

[0083] The adhesive sheet is an adhesive sheet for a flexible image display device used when forming a laminate constituting a flexible image display device. Specifically, the adhesive sheet is used when the adhesive layer is attached to an adherend. Here, the adhesive sheet of the present embodiment has the adhesive layer and the spacer of the present embodiment. The adhesive sheet can be in a form in which a spacer is stacked on one of the surfaces of the adhesive layer, or in a form in which the two surfaces of the adhesive layer are clamped by a spacer, and any one of the forms is also included. Among these, the form of sandwiching the two surfaces of the adhesive layer is preferred.

[0084] [Spacer]

[0085] The spacer is a release sheet or a release film that is peeled off from the adhesive layer when forming a laminate constituting a flexible image display device. The spacer has, for example, a release layer formed by applying a release agent on a substrate such as paper, a plastic film, or a synthetic paper. Examples of the release agent include silicone, alkyd resin, melamine resin, fluororesin, and acrylic resin. In addition, the thickness of the spacer is not particularly limited, but is about 10 μm to 200 μm.

[0086] <Laminate for flexible image display device>

[0087] As an example of using an adhesive sheet for a flexible image display device, first peel off the spacer on one side and laminate the adherend on the exposed adhesive layer. Next, peel off the other spacer facing each other and laminate the exposed adhesive layer to a polarizing plate or a transparent conductive film, thereby forming a laminate constituting a flexible image display device. Here, the laminate of the present embodiment is formed by using the adhesive sheet of the present embodiment, and therefore refers to a laminate having an adhesive layer of the present embodiment attached to an adherend. In addition, a hard coating layer, an easy-to-attach coating layer, etc. can be laminated on the laminated surface of the adhesive layer and the adherend.

[0088] <Flexible image display device>

[0089] One of the important features of the flexible image display device of this embodiment is that it has a bending function, and includes the laminate of this embodiment and an organic electroluminescence (hereinafter also referred to as "EL") display panel that can be bent. The flexible image display device is configured such that a laminate for a flexible image display device is arranged on the visual recognition side relative to the organic EL display panel, and can be bent. In addition, a liquid crystal panel may be used instead of the organic EL display panel, and a window may be arranged on the visual recognition side relative to the laminate for the flexible image display device.

[0090] The flexible image display device can be preferably used as a flexible liquid crystal display device, an organic EL display device, a plasma display panel (PDP), an electronic paper, or other image display device. In addition, the flexible image display device can be used regardless of the touch screen method such as a resistive film method or an electrostatic capacitance method.

[0091] Example

[0092] Hereinafter, the present disclosure will be described based on the embodiments. In addition, the present disclosure is not limited to the following embodiments, and the following embodiments can be deformed and changed based on the main idea of ​​the present disclosure, and these deformations and changes should not be excluded from the scope of the present disclosure. In addition, the following "parts" and "%" are values ​​based on "parts by weight" and "% by weight", respectively.

[0093] <Measurement of weight average molecular weight (Mw)>

[0094] The weight average molecular weight (Mw) was measured using GPC "LC-GPC System" manufactured by Shimadzu Corporation. The weight average molecular weight (Mw) was determined by conversion using polystyrene having a known molecular weight as a standard substance.

[0095] · Device name: LC-GPC system “Prominence” manufactured by Shimadzu Corporation.

[0096] · Pipe string: Four GMHXL pipes manufactured by Tosoh Corporation and one HXL-H pipe manufactured by Tosoh Corporation are connected.

[0097] Mobile phase solvent: tetrahydrofuran.

[0098] Flow rate: 1.0 mL / min.

[0099] Column temperature: -30℃.

[0100] <Synthesis Example of Acrylic Adhesive>

[0101] In a reaction container (hereinafter referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, a dropping device, and a nitrogen introduction tube, the monomers and 2,2'-azobisisobutyronitrile (AIBN) described in Table 1 are added at the contents described in Table 1, respectively, and the environment in the reaction container is replaced with nitrogen. Then, the reaction is started while stirring at 50°C under a nitrogen environment. Then, the reaction solution is reacted at 50°C for 4 hours. After the reaction is completed, it is cooled and diluted with ethyl acetate to obtain an acrylic adhesive containing a (meth) acrylic acid copolymer with a non-volatile component of 30% and a viscosity of 3000mPa·s. The weight average molecular weight (Mw) of the obtained acrylic adhesive (the (meth) acrylic acid copolymer constituting it) is shown in Table 1. In addition, the blank column in the table indicates that it is not formulated.

[0102]

[0103] The details of the monomers described in Table 1 are as follows.

[0104] ·2EHA: 2-ethylhexyl acrylate.

[0105] ·BA: Butyl acrylate.

[0106] IBXA: Isobornyl acrylate.

[0107] ·CH: Cyclohexyl acrylate.

[0108] ·DOA: dodecyl acrylate.

[0109] ·ODA: Octadecyl acrylate.

[0110] AA-6: macromonomer (single-terminal methacryloyl polymethyl methacrylate, number average molecular weight 6000 (manufactured by Toagosei Co., Ltd.)).

[0111] AK-32: macromonomer (single-terminal methacryloyl polydimethylsiloxane, number average molecular weight 20,000 (manufactured by Toagosei Co., Ltd.)).

[0112] AA: Acrylic acid.

[0113] HBA: 4-hydroxybutyl acrylate.

[0114] ·Am: Acrylamide.

[0115] <Adhesive Sheet Production>

[0116] With respect to 100 parts of the adhesives described in Tables 2 and 3, the hardeners described in Tables 2 and 3 were prepared in a predetermined amount, and ethyl acetate was further added to obtain an adhesive composition in which the non-volatile component was adjusted to 20%. The obtained adhesive composition was applied to a polyethylene terephthalate separator having a thickness of 75 μm so that the thickness after drying was 50 μm, and hot air dried at 100° C. for 2 minutes to form an adhesive layer. Next, a PET separator having a thickness of 50 μm was attached to the adhesive layer to obtain an adhesive sheet.

[0117] <Measurement of gel fraction>

[0118] The adhesive sheet was cut into a size of 30 mm × 100 mm, the separator on one side was peeled off, and the exposed adhesive layer was attached to a weighed 300-mesh stainless steel mesh (weight W0), and the other separator was peeled off to prepare a sample. The weight obtained by weighing the sample was set as W1, and the sample was allowed to stand in ethyl acetate for 24 hours, dried at 100°C for 1 hour, and weighed. The weight obtained by weighing was set as W2, and calculated using the following formula (2).

[0119] [Formula 2]

[0120] Gel fraction (%) = {(W2-W0) / (W1-W0)}×100···(2).

[0121] <Measurement of storage elastic modulus at -30°C>

[0122] Two sets of sheets with spacers peeled off from one side of the adhesive sheet are prepared, and the adhesive layers are bonded to each other using a laminator to form a laminate of spacer / adhesive layer / spacer. The spacer on one side of the laminate is peeled off and repeatedly bonded to form a laminate of an adhesive layer with a thickness of 1 mm. For the laminate, the storage elastic modulus G' is measured by a rheometer (manufactured by TA Instruments, DHR-2) using a φ8mm measuring probe under the conditions of a strain of 0.1%, a frequency of 1Hz, and a heating rate of 10°C / min from -70°C to 200°C.

[0123] <Measurement of deformation α and recovery rate>

[0124] Prepare two groups of sheets with spacers peeled off from one side of the adhesive sheet, and use a laminator to bond the adhesive layers to each other to form a laminate of spacer / adhesive layer / spacer. Peel off the spacer from one side of the laminate and repeat bonding to form a laminate of an adhesive layer with a thickness of 1 mm. For the laminate, a rheometer (manufactured by TA Instruments, DHR-2) with a φ8mm measuring probe is used, and the deformation amount when a strain of 20 kPa is given for 5 minutes at 25°C using parallel plates is set to the deformation amount α, and the residual deformation amount after 5 minutes after the strain after measuring the deformation amount α is set to 0 KPa and β, and the "recovery rate" is calculated using the formula (1).

[0125] <Adhesion of adhesive layer to colorless polyimide>

[0126] The spacer on one side of the adhesive sheet is peeled off and attached to a 50μm PET film using a laminator. Then, another spacer is peeled off and attached to the corona-treated surface of a 50μm thick colorless polyimide (manufactured by KOLON) on one side of which a corona treatment with an output power of 300W is implemented using a laminator. Thereafter, the components are kept in close contact in an autoclave at 50°C and 5 atmospheres for 20 minutes to obtain a measurement sample. After the measurement sample is placed at 23°C for 1 day, a tensile tester ("TENSILON" manufactured by ORIENTEC) is used to measure the adhesion at a peeling speed of 300mm / min and a peeling angle of 180° in an environment of 23°C and a relative humidity of 50%.

[0127] <Evaluation of whitening of the bent portion and displacement of the end portion by bending test>

[0128] The separator is peeled off from the produced adhesive sheet, and the exposed adhesive layer is pasted to colorless polyimide (manufactured by KOLON, 50μm) by a laminator under an environment of 25°C and a relative humidity of 50%. Another separator is peeled off and adhered to a PET film with a thickness of 188μm by a laminator to obtain a test laminate including PET film / adhesive layer / colorless polyimide. Secondly, for the test laminate, as a normal test, a bending tester (manufactured by Yuasa-system Machinery Co., Ltd.) is used under an environment of 25°C and a relative humidity of 50%, and the inner diameter (diameter) during bending is set to 6mm. The bending and opening at 180° are repeated for 300,000 times as one cycle. In addition, a test was also carried out under the condition that the inner diameter (diameter) was changed to 3mm. The whitening of the bent part and the displacement of the end are evaluated according to the following criteria for the appearance after the test.

[0129] Appearance: The presence of bubbles in the test laminate and the presence of lifting or peeling of the adhesive layer were visually evaluated under the following conditions (five-step evaluation).

[0130] [Whitening of the curved part]

[0131] 5: No bubbles are observed within 5 mm to the left and right of the bending part.

[0132] 4: There are less than 10 bubbles within 5 mm on both sides of the bending part.

[0133] 3: There are 11 or more and 50 or less bubbles within a range of 5 mm to the left and right of the bent part.

[0134] 2: There are 51 or more and less than 100 bubbles within a range of 5 mm to the left and right of the bending part.

[0135] 1: There are more than 100 bubbles within a range of 5 mm to the left and right of the bend.

[0136] [End offset]

[0137] 5: The offset between the PET film and the polarizing plate is less than 1mm.

[0138] 4: The offset between the PET film and the polarizing plate is greater than 1 mm and less than 2 mm.

[0139] 3: The offset between the PET film and the polarizing plate is greater than 2 mm and less than 3 mm.

[0140] 2: The offset between the PET film and the polarizing plate is 3 mm or more and less than 4 mm.

[0141] 1: The offset between the PET film and the polarizing plate is 4 mm or more.

[0142]

[0143]

[0144] The details of the commercially available adhesives, hardeners, and additives listed in Tables 2 and 3 are as follows.

[0145] (Commercially available adhesive)

[0146] ·R16: TUFTEC H1272: Hydrogenated styrene elastomer (SEBS), manufactured by Asahi Kasei Corporation.

[0147] R17: LA2330: PMMA-PnBA-PMMA triblock copolymer, Mw: 99400, PMMA / PnBA=20 / 80 (mass ratio), manufactured by Kuraray.

[0148] R18: LA4285: PMMA-PnBA block copolymer, Mw: 60,000, PMMA / PnBA=55 / 45 (mass ratio), manufactured by Kuraray.

[0149] (Hardener)

[0150] D-110N: a trimethylolpropane adduct of xylylene diisocyanate as a polyisocyanate compound.

[0151] D-160N: a trimethylolpropane adduct of hexamethylene diisocyanate as a polyisocyanate compound.

[0152] EX-313: Multifunctional epoxy compound (glycerol polyglycidyl ether)

[0153] ·PZ-33: trifunctional aziridine compound.

[0154] CAT-PL-50T: Platinum catalyst, manufactured by Shin-Etsu Chemical Co., Ltd.

[0155] (additive)

[0156] FTR6100: Styrene monomer / aliphatic monomer copolymer, softening point 95°C, manufactured by Mitsui Chemicals.

[0157] Industrial Applicability

[0158] As described above, the present disclosure is applicable to a flexible image display device, an adhesive layer used in a laminated body constituting the device, and an adhesive sheet using the adhesive layer.

Claims

1. An adhesive layer for a flexible image display device, wherein the adhesive layer is characterized in that: In the adhesive layer, The gel fraction is 55% to 90%. The storage elastic modulus at -30°C is 0.1 MPa or more and 8 MPa or less, The deformation amount α when a strain of 20 kPa is applied by parallel plates at 25°C for 5 minutes using a measuring probe of φ8 mm is 100% to 800%, and The recovery rate calculated by the following formula (1) is 70% or more. The adhesive layer is formed using an adhesive composition including an acrylic adhesive and a curing agent. Recovery rate = (α - β) / α × 100 (β represents the residual deformation after 5 minutes when the strain is set to 0 kPa after measuring α)...(1). 2 . The adhesive layer according to claim 1 , wherein the adhesive force to the adherend is 10 N / 25 mm to 50 N / 25 mm.

3. The adhesive layer according to claim 1 or 2, wherein the acrylic adhesive comprises a (meth)acrylic acid copolymer made from a monomer mixture as a raw material, wherein the monomer mixture contains an alicyclic monomer and / or an acrylic monomer having a linear alkyl group having 10 to 20 carbon atoms, and an acrylic monomer having a branched alkyl group having 6 or more carbon atoms. 4 . The adhesive layer according to claim 3 , wherein the (meth)acrylic copolymer has a weight average molecular weight (Mw) of 1,000,000 or more. 5 . An adhesive sheet comprising the adhesive layer according to claim 1 and a separator. 6 . A laminated body, wherein the adhesive layer according to claim 1 is attached to an adherend.

7. A flexible image display device comprising the laminated body according to claim 6.

Citation Information

Patent Citations

  • Adhesive for repeated bending device, adhesive sheet, repeated bending laminate member and repeated bending device

    JP2020139034A

  • Low dielectric constant optically clear adhesives for flexible electronic displays

    JP2020513451A